Application of Florence Nightingale’s Environmental Theory to Pulmonary TB in Fishermen and Smoked Fish Industry Workers - Darwis, Darwis; Muzakkir; Erviana; Muzdalia, Ika; Maharja, Rizky (An Overview of Disease and Health Research Vol. 2, 2025)
Introduction: The process of smoking fish in Indonesia is still carried out traditionally and can affect the fishermen and smoked fish industry communities who have pulmonary Tuberculosis (TB). The environmental impact that commonly occurs as a result of smoked fish processing activities is air pollution due to the smoke that arises. Florence Nightingale, often celebrated as the icon of modern nursing, proposes a theory emphasising the critical role of the environment in health and recovery. She believes that a healthy environment is necessary for proper treatment and maintenance of health. Aim: This study aims to apply the Florence Nightingale Theory in cases of pulmonary TB among fishermen and the smoked fish industry communities. Materials and Methods: This investigation was conducted in the Somba area, West Sulawesi, which is one of the areas with the most smoked fish industry in West Sulawesi. This study used an analytic observational method with a case-control design. This study used non-probability sampling and purposive sampling techniques with the sample. The number of respondents was 106, consisting of 53 respondents in the case group and 53 respondents in the control group. The data obtained were then analysed using Chi-Square. Results: Findings reveal that the environment exposed to smoke from smoking fish, smoking habit, and window opening habit have an influence on the incidence of pulmonary TB. This follows the emphasis of Nightingale's environmental theory, stating that pure air and lighting are included in the main components influencing the environment. The environment exposed to smoke from smoking fish has a p-value of 0.001 with OR 3.718, smoking habit has a p-value of 0.034 with OR 2.842, and window opening habit has a p- p-value of 0.000 with OR 0.391. Whereas, occupancy density and cooking fuel have no influence on the incidence of pulmonary TB, as evidenced by statistical tests with a p-value of >0.005. Conclusion: The incidence of pulmonary TB in fishermen and smoked fish industry communities is influenced by the environment exposed to smoke from smoking fish and the window opening habit. This follows the emphasis of Nightingale's environmental theory, stating that pure air and lighting are included in the main components influencing the environment.